2011
DOI: 10.1063/1.3532084
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic detection of the most stable carbonic acid, cis-cis H2CO3

Abstract: Carbonic acid had not been detected by any spectroscopic means for a long period. Recently, we have reported the detection of its second most stable conformer, cis-trans H(2)CO(3), as the first spectroscopic detection of the isolated carbonic acid molecule. In the present work, the most stable conformer of carbonic acid, cis-cis H(2)CO(3), in the gas phase has been successfully produced in a supersonic jet using a pulsed discharge nozzle, and pure rotational transitions of this molecule have been observed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 20 publications
4
64
0
2
Order By: Relevance
“…The cis-cis form of carbonic acid (LM1) is a global minimum on the H 2 CO 3 potential energy surface, and has been observed experimentally (Bernand et al, 2011;Mori et al, 2011). The cis-trans form (LM2) has been produced and identified by Endo and co-workers (Mori et al, 2009), and is the second most stable conformer with an energy above LM1 by only 1.56 kcal mol À1 .…”
Section: Structural Isomers and Isomerizationsmentioning
confidence: 95%
See 1 more Smart Citation
“…The cis-cis form of carbonic acid (LM1) is a global minimum on the H 2 CO 3 potential energy surface, and has been observed experimentally (Bernand et al, 2011;Mori et al, 2011). The cis-trans form (LM2) has been produced and identified by Endo and co-workers (Mori et al, 2009), and is the second most stable conformer with an energy above LM1 by only 1.56 kcal mol À1 .…”
Section: Structural Isomers and Isomerizationsmentioning
confidence: 95%
“…The LM2 form is the second most stable conformation of carbonic acid; and is an important intermediate to its dissociation products, CO 2 and H 2 O. Very recently, the spectra of the most stable carbonic acid, cis-cis form, have been identified in the microwave (Mori et al, 2011) and infrared (Bernand et al, 2011) regions. Adamczyk et al (2009) reported the generation of deuterated carbonic acid in D 2 O solution by ultrafast protonation of bicarbonate.…”
Section: Introductionmentioning
confidence: 98%
“…In this context, it may be of interest that carbonic acid, OC(OH) 2 , is fairly stable in water-poor environments, in particular at low temperatures, and that it can be transferred into the gas phase without complete decomposition (Bernard et al 2013). The microwave spectrum of carbonic acid was also recorded recently by Mori et al (2011). And while OS(OH) 2 is, to our knowledge, not stable in the gas phase, O 2 S(OH) 2 , sulfuric acid, is, and its rotational spectrum was studied extensively quite recently by Cohen & Drouin (2013).…”
Section: Discussionmentioning
confidence: 99%
“…As described in a very recent review [7], carbonic acid has been well studied in both the gas phase [8][9][10] and in cryogenic matrixes [11][12][13][14][15], but there have been very few successful spectroscopic studies of the aqueous acid, and none of its electronic structure [16][17][18]. Carbonic acid is intrinsically unstable upon contact with even a single water molecule, reacting via a proton chain mechanism to rapidly form aqueous bicarbonate, carbonate, and hydrated protons [19][20][21], which comprises the reversible mechanism for dissolution of CO 2 gas.…”
Section: Introductionmentioning
confidence: 99%